Confrontation of endolymphatic hydrops diagnosis on 3-Tesla MRI to clinical and audiovestibular findings in Meniere's disease - Diorflar, Sarah; Guigou, Caroline; Daguet, Edouard; Bensimon, Jean-Loup; Toupet, Michel; Bozorg-Grayeli, Alexis (Frontiers in Neurology, 2023)
Objective The aim of this study was to compare different MRI diagnostic criteria for endolymphatic hydrops (EH) and to investigate the relation between audiovestibular and MRI findings in Meniere's disease (MD). Materials and methods Prospective cross-sectional cohort study in 2 referral centers included 76 patients with unilateral (n = 62) or bilateral (n = 14) MD. All patients underwent inner ear 3T-MRI 4 h (n = 52) or >24H (n = 24) following audiovestibular tests. T2-CISS and 3D-FLAIR images 4H after gadolinium were obtained. EH diagnosis was based on saccular morphology on coronal views (T2 and 3D-FLAIR), semi quantitative estimation of endolymphatic space enlargement, and saccule utricle ratio inversion (SURI) on 3D-FLAIR axial views. Results SURI was the best criterion related to the disease side (43 SURI+ on symptomatic ears, n = 77, vs. 6 SURI+ on asymptomatic ears, n = 53, p < 0.0001, Chi-2). Same-day MRI revealed relation between EH, hearing loss and caloric weakness which could not be detected on delayed MRI: SURI was associated with a higher pure-tone average (43 ± 4.1 dB in SURI+ ears, n = 42 vs. 23 ± 2.6 SURI-, n = 62, p < 0.0001, unpaired t-test,), and a higher proportion of vestibular caloric weakness (23/46 SURI+ ears vs. 4/62 SURI-, p < 0.001, Chi-2). Among all criteria, SURI combined to caloric weakness was the best predictor of the affected side in a logistic regression model. Conclusion SURI had the strongest relation to the side the disease and audio vestibular findings for unilateral, probable and definite meniere disease. A short delay between MRI and audio vestibular tests improved the coherence between the findings.